ADHERENCE TO IRON AND FOLIC ACID SUPPLEMENTATION AND PREVALENCE OF ANAEMIA AMONG PREGNANT WOMEN AT A TERTIARY CARE HOSPITAL - Palikhey , Anjan; Prajapati , Pravash; Yadav , Anita; Shrestha , Jharana; Subedi , Jigyasa; Shrestha , Laxmi; Shrivastava , Amit Kumar; Yadav , Chandrajeet Kumar (Journal of Chitwan Medical College, 2022)
Background: Anaemia is characterized by a reduced oxygen-carrying capacity of blood and causes various health problems in people of all ages, including pregnant women. The most common cause of anemia is a lack of iron in the diet. Prevention of anaemia requires strict adherence to iron and folic acid supplementation during pregnancy. The main objective of this study was to gather information on adherence to iron and folic acid supplementation and anaemia prevalence among pregnant women. Methods: The cross-sectional study was conducted among 200 postpartum mothers in the obstetrics ward of Universal College of Medical Sciences. Eligible participants were interviewed using a questionnaire to measure their adherence to iron and folic acid supplementation during pregnancy. Haemoglobin levels were recorded to check the presence of anaemia. Multivariable regression analysis was used to find the relationship between independent and dependent variables. Results: Total 164 (82%) participants had good adherence to iron and folic acid supplementation. Participants who started their antenatal care visit in first trimester were more adherent to iron and folic acid supplementation (AOR = 0.13, 95% CI (0.05–0.39)). The prevalence of anaemia was 24%. Anaemic participants were less likely to adhere to their iron and folic acid supplements (AOR = 0.26, 95% CI (0.11–0.63)). Conclusions: The adherence of participants to iron and folic acid supplementation was good and significantly associated with gestational age when antenatal care visit was started, child birth weight and anaemia. By strengthening the national level awareness campaign, we can further improve the adherence rate and prevent anaemia.